Partnerships dan Pemberdayaan Masyarakat dalam Pengembangan Posdaya Usia Reproduksi dan Lansia di Nagari Sumaniak - Yulizawati Yulizawati; Lusiana Elsinta Bustami; Aldina Ayunda Insani; Fitrayeni Fitrayeni; Feni Andriani; Erda Mutiara Halida; Rafika Oktova; Ulfa Farrah Lisa; Laila Rahmi; Uliy Iffah; Miranie Safaringga (Warta Pengabdian Andalas, 2019)
Nagari Sumaniak is a nagari whose productive age has mostly left her hometown to migrate because the natural resource potential in this nagari is very low. So there are many elderly people living in this area and most of them are less noticed and their health condition is very vulnerable. The method used by conducting surveys and interviews. Together with the nagari community, they hold a meeting to overcome the existing problems in Nagari. PKM activities were carried out by: 1) Carrying out Communication, Information and Education (IEC) activities on Parenting in the Sumaniak community, especially for women of childbearing age couples, 2) Carrying out pregnancy inspection activities, 3) Carrying out simple labor inspection activities and consultation with a Doctor, and 4) Carry out gymnastics activities with a Healthy Heart at the Wali Nagari Sumaniak Office in Tanah Datar District. The entire series of PKM activities was carried out well with support provided by various parties both from the Nagari apparatus and the surrounding residents. It was expected that the activities of providing Communication, Information and Education (IEC) on Parenting in the Sumaniak community.